Collaborative Governance of College Students’ Psychological Issues and Campus Safety: Correlation, Causes, and Construction of Response System - Niu, Zhuojiang (Journal of Research in Vocational Education, 2026)
This article systematically explores the intrinsic correlation between psychological issues among college students and campus safety, as well as the multidimensional causes and the construction of a comprehensive prevention and control system. The study points out that psychological issues are the core hidden danger source of campus safety, which not only easily leads to individual emergencies but also may form group safety risks through emotional contagion and network diffusion. The causes of psychological issues cover multiple dimensions such as lack of family support, academic and environmental adaptation pressure, insufficient individual psychological resilience, and social environmental impacts. Therefore, a three-dimensional early warning system that includes dynamic data monitoring, full participation in early warning, and home-school collaboration should be established, and a rapid intervention mechanism that encompasses graded response, multi-departmental linkage, and professional referral should be improved. In terms of long-term construction, it is necessary to strengthen psychological recovery after problems, improve curriculum education and peer support networks, and focus on creating an inclusive campus culture, optimizing the physical environment and evaluation system, thereby forming an integrated working closed loop of “early warning-response-recovery-support” to effectively enhance the level of campus psychological safety.